Economic burden of cancer in China: causes and reflection - Dan-hong SONG; Fang-hui ZHAO; Yong ZHANG (Editorial Office of Chinese Journal of Public Health, 2023)
Over recent years in China, the incidence and mortality of cancer have increased significantly, bringing a heavy economic burden on patients, patients' families and society. In this paper, we analyze main causes and heavy economic burden of cancer in China from aspects of disease characteristics and related social factors, and put forward suggestions on reducing the economic burden of cancer in China in the future.